(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
One of the most difficult areas of purulent surgery is the development of a surgical infection of soft tissues against the background of diabetes mellitus, when necrotic changes dominate. To accelerate the process of cleansing and subsequent healing of soft tissue wounds in patients with diabetes mellitus, antibacterial drugs, proteolytic enzymes, as well as ointment dressings are used, depending on the stage of the wound process using methods physical impact. In this regard, the purpose of this study is: to study the antibacterial and anti-inflammatory effect of the drug FarGALS in necrotic infections of soft tissues against the background of diabetes mellitus. Studies were conducted in 103 patients with purulent-inflammatory diseases who were on inpatient treatment at the Republican Center for Purulent Surgery and Surgical Complications of Diabetes Mellitus.